О насекомых, паразитирующих в пауках, их коконах и гнездах - Пичка, В.Е. (Вестник зоологии, 1977)
Eight species of Hymenoptera: Gelis melanocephala S c h r a n k., Hemiteles melanopygus G r a v., Hemiteles sp., Hidryta [rater Cresson., Trychosis molestus Tschek., Zaglyptus varipei G r a v., Zatypota percontatoria M u 11. family (Ichneumonidae), Pediobius sp. (Eulophidae) and one species of flies, Oncodes gibbosus L., parasitizing in eleven species of spiders, their cocoons and nests were found in the territories of the Voronezh and Kursk Central-Chernozemian reservations.